EFEKTIFITAS JARAK TANAM DAN JUMLAH BENIH PER LUBANG TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI PADI GOGO - Agus Hariadi Pinem; Asil Barus; Chairani Hanum (Jurnal Agroekoteknologi, 2013)
Effectiveness of different planting distance and number of seedlings per hill on growth and yield ofUpland Rice, supervised by Ir. Asil Barus, MS. and Dr. Dra. Ir Chairani Hanum, MS. The researchwas conducted in the field UPT BBI, at an altitude ± 57 m above sea level in April-July 2012 usingRandomized Block Design (RBD) factorial with two factors which are different planting (20 x 20cm, 20 x 25 cm , 20 x 30 cm) and the number of seedlings (2, 3, 4, 5, 6 seed /hill). The parametersmeasured were plant height, number of tillers, dry weight of the canopy, the canopy destructive dryweight, root dry weight, number of panicle, number of grain hollow, productive grain number, grainweight for each hill, 1000 grain weight and production for each plot. The results showed that allparameters significantly affected by the diiferent planting distance and number of seedlings per hilltreatment plant height, canopy dry weight, root dry weight, number of grain productive, and 1000grain weight.Keywords: